Soil pollution and agriculture in sub-Saharan Africa: State of the knowledge and remediation technologies - Tindwa, Hamisi J.; Singh, Bal Ram (Frontiers in Soil Science, 2023)
The sub-Saharan Africa (SSA) region bears the blunt of soil pollution mainly due to-haphazard disposal and gross mismanagement of a wide assortment of pollutants generated from within and outside the region. Pollution of agricultural soils in the region is so intense that out of the 80 countries substantially affected by land degradation (soil pollution, inclusive) in the world, 36 are found in Africa, the SSA, in particular. Pollution of soils has resulted into a significant reduction in their ability to support crop growth and yield apart from jeopardizing safety and security of agricultural produce in SSA. Consequences of pollution of soils on human health in the region are inadequately reported, but they range from non-fatal, life-changing effects like skin damage due to acute, invariably fatal incidences of exposure to milt by chronic effects. We show in this review, that while science and advancement in technology has provided a multitude of alternative techniques to pollution control and remediation of affected soils, such techniques are largely inaccessible to most SSA countries. There is also lack of coordination on development, enforcement and implementation of legal and political instruments to tackle the growing risk of pollution to human health from soil contamination across the SSA region. Couple with this, lack of data on status of soil pollution in most SSA countries affects the countries’ capacity to devise and plan policies that can help reduce soil pollution. Countries need to maximize efforts to reverse the status of already polluted pieces of land through strengthening remediation programs, research on how best to gather, maintain and complement soil pollution data and actions that inform decision-making.